Bai` bithaman ajil home financing in Malaysia: An evaluation - Suraya, Ismail; Wan Anisah, Endut (2015)
The discussion on Shariah concepts in home financing products is not new. However, this matter is always seen relevant with Islamic finance. Based on bai` bithaman ajil (BBA) home financing, this paper tries to examine the practice among Islamic banking institutions compared to views of Shariah advisors in Malaysia. Even though BBA home financing is said to have many weaknesses, but most of the Islamic banking institutions are seen to offer such products on the market. The question is, how about the views and the stands of the Shariah advisors towards this Shariah concept? This question will be answered based on the primary information from Shariah advisors. The results show that most of the Shariah advisors do not agree with this BBA practice. These findings demonstrate a difference in views that occurs between the Shariah advisors and the practice in Islamic banking institutions in Malaysia.